Jati Denok: Big Book Media as an Effort to Improve Poetry Reading Skills of Second Grade Students in Elementary School - Afifah, Nur Ummi; Purwati, Panca Dewi; Sismulyasih SB, Nugraheti (MIMBAR PGSD Undiksha, 2024)
The low level of reading skills is one of the fundamental problems that occurs in elementary schools. Low initial reading skills indicate this. This research aims to develop learning media in the form of the Big Book "Jati Denok". The research method used is R&D (Research and Development) with the Borg and Gall design. The research subjects are material experts, media experts and language experts. The test subjects were 21 students and teachers. Data collection methods include observation, interviews, documentation, questionnaires, and tests. The main instrument is a questionnaire. Analyzed using both qualitative and quantitative descriptive techniques. The study results show that media experts rated the feasibility test as very feasible, with an average score of 94.4%. Material experts' validation results rated the content as very feasible, with an average score of 93.75%. The results of validation by language experts were the same as those of material experts, obtaining appropriate criteria with an average value of 93.75%. The student and teacher response questionnaires in the trial both scored 100% (very good). In addition, the analysis results show an increase in students' poetry reading skills. It can be concluded that the media innovation in the form of the Big Book “Jati Denok” is declared feasible and can improve poetry reading skills in grade II elementary school students.